Generalized Pustular Psoriasis in a 4 Year-old - Boy Rievanda; Ayu Natasya; Diana Wijayati (PT Kalbe Farma Tbk., 2022)
Background: Generalized pustular psoriasis (GPP) is a variant of psoriasis characterized by widespread erythematous skin studded with sterile pustules. In general, PPG is rare in children. Diagnosis is made from the clinical and histopathological examination. The rarity of GPP in children has resulted in a need for standardized guidelines. Case: A 4 year-old boy with a generalized pustular eruption and confluent scaly plaques on erythematous skin. Mild pruritus and general malaise were present. Histopathological examination confirmed diagnosis of GPP. Clinical improvement was achieved with a combination of topical corticosteroids, anti-histamine, and systemic corticosteroids for two weeks. Conclusion: A combination of topical corticosteroids, anti-histamine, and systemic corticosteroids can still achieve clinical improvement in children with GPP. Nevertheless, its adverse effects should always be considered, and strict monitoring is required. Latar Belakang: Psoriasis pustulosa generalisata (PPG) merupakan salah satu varian klinis psoriasis yang ditandai oleh kulit eritema disertai erupsi pustul steril yang tersebar luas. Pada umumnya, PPG jarang pada anak-anak. Diagnosis berdasarkan pemeriksaan klinis dan histopatologis. Jarangnya kasus PPG pada anak-anak menyebabkan kurangnya pedoman tata laksana terstandarisasi. Kasus: Seorang anak laki-laki berusia 4 tahun dengan kelainan kulit berupa erupsi pustulosa generalisata beserta kumpulan plak berskuama pada dasar kulit eritema. Keluhan disertai gatal ringan serta rasa lemah dan lesu. Pemeriksaan histopatologis memperkuat diagnosis PPG. Perbaikan klinis tercapai dengan tata laksana kombinasi corticosteroid topikal, anti-histamin, dan corticosteroid sistemik selama 2 minggu. Simpulan: Kombinasi corticosteroid topikal, anti-histamin, dan corticosteroid sistemik mampu menghasilkan perbaikan klinis pada anak-anak dengan PPG. Meskipun demikian, efek sampingnya harus selalu diperhitungkan dan membutuhkan pengawasan ketat.